2008
DOI: 10.5194/acp-8-6103-2008
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of stratospheric and mesospheric temperatures from MLS and SABER into a global NWP model

Abstract: Abstract. The forecast model and three-dimensional variational data assimilation components of the Navy Operational Global Atmospheric Prediction System (NOGAPS) have each been extended into the upper stratosphere and mesosphere to form an Advanced Level Physics High Altitude (ALPHA) version of NOGAPS extending to ∼100 km. This NOGAPS-ALPHA NWP prototype is used to assimilate stratospheric and mesospheric temperature data from the Microwave Limb Sounder (MLS) and the Sounding of the Atmosphere using Broadband … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 56 publications
(63 reference statements)
3
84
0
Order By: Relevance
“…Compared to temperature data from the SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) instrument (Mlynczak and Russell, 1995) the MLS temperature has a negative bias uncertainty of up to 9 K (Schwartz et al, 2008). MLS temperatures in combination with SABER data have been used in the assimilation system NOGAPS-ALPHA (Hoppel et al, 2008;Eckermann et al, 2009). A comparison of the MLS temperatures used in our study with the corresponding assimilated temperatures (not shown) does not reveal a clear pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to temperature data from the SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) instrument (Mlynczak and Russell, 1995) the MLS temperature has a negative bias uncertainty of up to 9 K (Schwartz et al, 2008). MLS temperatures in combination with SABER data have been used in the assimilation system NOGAPS-ALPHA (Hoppel et al, 2008;Eckermann et al, 2009). A comparison of the MLS temperatures used in our study with the corresponding assimilated temperatures (not shown) does not reveal a clear pattern.…”
Section: Resultsmentioning
confidence: 99%
“…This dataset is used to search for the top border of the SPW1 in geopotential heights. The description of NOGAPS-ALPHA can be found in Hoppel et al (2008) and Eckermann et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…The background error variance for water vapor in the upper atmosphere was set large enough to ensure that the analysis was highly constrained to the observations, producing a zonal mean distribution that is nearly identical to the MLS data. For further details of the assimilation system, see Hoppel et al (2008).…”
Section: Chem2d-h2o In Nogaps-alphamentioning
confidence: 99%
“…The model uses the non-orographic gravity wave drag parameterization of Garcia et al (2007) with the same settings as in E2008. The T79L68 model is initialized with analyzed winds, temperature, and constituents (e.g., O 3 and H 2 O) produced by the NOGAPS-ALPHA DA component, which is described in detail by Hoppel et al (2008) and E2008. From the surface to the mid-stratosphere, these NOGAPS-ALPHA analyses are based on assimilation of conventional meteorological data sets used by the operational T239L30 system.…”
Section: Chem2d-h2o In Nogaps-alphamentioning
confidence: 99%